Interdisciplinary Approach in Primary Education: Animated Films as a Tool for Cross-Cultural Awareness - Huber, Loreta (Revija za elementarno izobraževanje, 2025)
The paper presents results from a study exploring the effectiveness of animated films in primary education for enhancing cross-cultural awareness. The study examined how animated films can broaden young learners’ perspectives on diverse cultural practices, values, and traditions, and identified factors that affect information processing in complex, cross-cultural contexts. Using triangulation, data were gathered and analysed from twenty primary students (ages 8-11). The study employed Tobii Pro Glasses 3 for eye-tracking, supplemented by a questionnaire to support the eye-tracking findings. Analysis revealed that integrating culture-specific concepts from animated films can effectively enhance cross-cultural awareness in interdisciplinary education.
Keywords: interdisciplinary approach, multimodal education, cross-cultural awareness, animated films, eye-tracking.